Pemberdayaan Kelompok Usaha Perempuan Untuk Meningkatkan Daya Saing Di Era Bisnis Digital - Ali Imron; Rizka Ariyanti; M. Iqbal Notoatmojo (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2025)
The potential of women's business groups is still not maximized. There are still many female entrepreneurs who face many challenges in developing their businesses. Indonesian women must prepare themselves to enter the digital economic sector so that they can play a role, can benefit themselves, their families and their environment. In Api-Api village, Wonokerto District, activities were carried out to empower women's business groups to increase competitiveness in the digital business era. The benefits that will be received from this empowerment activity include: (1) women's business groups will be able to understand and implement digital business, (2) women's business groups will be able to manage their businesses well, (3) women's business groups will be able to understand the importance of business legality.